E-resource person directory of Faculty Computer & Mathematical Sciences / Siti Fatimah Mohd Rum and Rozmawati Mohd Yusof - Mohd Rum, Siti Fatimah; Mohd Yusof, Rozmawati (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Resource Person is a person amongst lecturers who has been appointed and given the mandate by the Ketua Pusat Pengajian to disseminate, to update and to preserve the information on the course under their supervision. But major problem occurs when lecturers try to reach these Resource Persons when they need to be updated with related matters for instance to get information on OBE's syllabus. Thus, it creates a minor-stressful event to lecturers when they failed to reach the Resource Persons. Hence, the idea is to produce an e-Resource Persons Directory for the Faculty of Computer & Mathematical Sciences using an e-book format. The e-Resource Person Directory will keep the information of Resource Person that includes pictures. This handy directory facilitates the Unit Pengurusan Kualiti to avoid the long-time searching of Resource Persons' information. We proposed the directory to be put as a source link on the UiTM Cawangan Melaka's website.